Pre-filtering antenna array for downlink TDD MC-CMA systems - Silva, Adão
This communication deals with downlink time division duplex MC-CDMA system, and presents a frequency domain pre-filtering technique, where the base station is equipped with an antenna array. We show that the space-filtering approach proposed allows to format the transmitted signals so that the multiple access interference at the mobile terminals is reduced allowing to transfer a significant part of the computational burden to the base station, and therefore enabling the use of a very low complex receiver at mobile. This approach uses the time division duplex channel reciprocity between uplink and downlink to obtain the channel state information. Simulation results are presented to demonstrate the effectiveness of the proposed pre-filtering algorithm.